Impact of artificial intelligence for agricultural sustainability - BHARTI, V. K.; BHAN, SURAJ; ., MEETALI; ., DEEPSHIKHA (Journal of Soil and Water Conservation, 2018)
The new agricultural technology strategy, artificial intelligence, integrated telematics, data management systems and auto-guidance solutions together, have the potential to make farming much more productive and profitable. The precision farming technologies help customers to become more efficient and save resources. Producing quality, nutritious and affordable food will be a huge challenge before the world. It is predicted that even with the limited resources, the smart ICT, a new hi-tech era need to be ushered in where automation and data can help farmers address the many challenges of the future. The Artificial Intelligence (AI) application in farming will bring revolution, sustainability and vibrancy in future farming. Through digital agriculture, where technologies such as Artificial Intelligence (AI), Cloud Machine Learning, Satellite Imagery and advanced analytics are empowering small-holder farmers to increase their income through higher crop yield and greater price control. The growth of artificial intelligence in agriculture is primarily driven by the increasing demand for agricultural production due to the increasing population, rising adoption of information management systems and new technologies for improving crop productivity, and increasing by implementing deep learning techniques, and growing initiatives by governments worldwide supporting the adoption of modern agricultural techniques. The only restraint in the growth of artificial intelligence in agriculture market is the high cost of gathering precise field data. Artificial intelligence can boost the efficiency of daily operations in a traditional farm and maximize production volume and minimize the possibility of failure due to natural disasters, system errors, and other factors by acquiring data on growth, the weather, and agricultural equipment.